Financial markets,instruments, and institutions - Santomero, Anthony M.; Babbel, David F. (Chicago : Irwin, 1997)
The book is on money and capital markets designed to be a one semester course within a finance department of a business school. the course does not need to overlap with monetary economics or finance topics taught else where in the curriculum. shoud a student choose totake no further courses in finance, this textbook offers a broad overview of financial markets, pricing and institutions.
Includes bibliographical references and index.
opc 26/02/15
Loans
Keywords: Financial services industry; Finance; Financial industry